Relative dose-response from solid-state and gel dosimeters through Monte Carlo simulations (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The present work compared the relative absorbed dose of some dosimetric materials, for energies of 250 kV and 6 MV, using PENELOPE and MNCPX codes. The composition of each material GD-301, TLD-100, MAGIC, and MAGAT were simulated and disposed of in a phantom filled with water following reference conditions recommended by the TRS-398 protocol. Percentage depth dose was used as a parameter of comparison. Since the obtained results with both codes were found a maximum difference of up to 2 % when compared the water material with experimental data before 6cm were found to a maximum difference of up to 2.2%  for 6 MV and 5.5 % for 250 kV.  Ratios between simulated PPD and experimental PDD values showed a maximum difference in the build-up region, for 6 MV, due to highsensitivityive from the incident fluency in the simulated and experimental conditions. The ratios for 250 kV showed significant differences from the simulated solid-state rather than gel dosimeters, due to its low energy, depth angular dependence from the solid-state dosimeter, as corroborating by literature. Even the differences showed for both codes, especially for lower energy, due to cross-the section database that implied the interaction probability for each Monte Carlo code, this method has been widely used to model radiation transport in several applications in medical physics, especially in dosimetry.